Connie : a memoir - Chung, Connie, 1946- (Grand Central Publishing, Hachette Book Group, 2024)
"In an industry dominated by white men, Connie Chung stood alone, the first and only Asian woman to break into the television news industry. This is her extraordinary story, told with incisive wit and remarkable candor. Connie Chung is a pioneer. In 1969 at the age of 23, this once-shy daughter of Chinese parents took her first job at a local TV station in her hometown of Washington, D.C. and soon thereafter began working at CBS news as a correspondent. Profoundly influenced by her family's cultural traditions, yet growing up completely Americanized in the United States, Chung describes her career as an Asian woman in a white male-centered world. Overt sexism was a way of life, but Chung was tenacious in her pursuit of stories - battling rival reporters to secure scoops that ranged from interviewing Magic Johnson to covering the Watergate scandal - and quickly became a household name. She made history when she achieved her dream of being the first woman to co-anchor the CBS Evening News and the first Asian to anchor any news program in the U.S. Chung pulls no punches as she provides a behind-the-scenes tour of her singular life. From showdowns with powerful men in and out of the newsroom to the stories behind some of her career-defining reporting and the unwavering support of her husband, Maury Povich, nothing is off-limits - good, bad, or ugly. So be sure to tune in for an irreverent and inspiring exclusive: this is CONNIE like you've never seen her before"--